2019
DOI: 10.1111/1467-9566.12986
|View full text |Cite
|
Sign up to set email alerts
|

Female family carers’ experiences of violent, abusive or harmful behaviour by the older person for whom they care: a case of epistemic injustice?

Abstract: Family carers affected by violent, abusive or harmful behaviour by the older person for whom they care face social and epistemic challenges in developing and sharing knowledge about their experiences. These difficulties have contributed to a situation in which there is a paucity of evidence and public discourse about how we understand violence and harm instigated by people who have care needs or are ‘vulnerable’. This paper reports the findings of a qualitative study that involved 12 in‐depth interviews with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 46 publications
(55 reference statements)
0
3
0
1
Order By: Relevance
“…Although 'caring' is a positive concept, it is important to note that some relationships may not be. As with other family relationships, caring dyads can be embedded in histories of family violence and abuse (Molyneaux et al, 2011;Isham et al, 2020). Other research, such as Mackay's (2017) exploration of social workers' roles in dealing with safeguarding concerns for an older couple where another relative is also involved, show a more complex understanding of care relationships.…”
Section: Care Dyadsmentioning
confidence: 99%
“…Although 'caring' is a positive concept, it is important to note that some relationships may not be. As with other family relationships, caring dyads can be embedded in histories of family violence and abuse (Molyneaux et al, 2011;Isham et al, 2020). Other research, such as Mackay's (2017) exploration of social workers' roles in dealing with safeguarding concerns for an older couple where another relative is also involved, show a more complex understanding of care relationships.…”
Section: Care Dyadsmentioning
confidence: 99%
“…Evidence indicates that people with dementia are particularly vulnerable, with challenging behaviour often cited as a trigger. Risk is heightened in contexts where the carer has been subject to abuse by the cared for person; this is not an uncommon experience for carers of relatives with dementia (Ash, 2014; Isham et al , 2020). In a study with well-defined target populations, 11%–20% of family carers reported physically abusing their relative (Cooper et al , 2009).…”
Section: The Nature Of Domestic Abusementioning
confidence: 99%
“…Lumpuhnya sektor ekonomi Indonesia dampak dari penyebaran covid-19 membuat banyak kepala keluarga terdampak dari pengurangan penghasilan hingga pemutusan kerja dan bagi mereka yang memiliki usaha dampak yang dirasa hingga harus gulung tikar, di sisi lain "dapur harus tetap ngebul" dan pengeluaran bahkan bukan semakin hemat tetapi semakin banyak keperluan karena perilaku baru, kebiasaan baru dan tuntutan baru selama masa new normal. Tekanan baru tersebut berupa risiko kesihatan fisik, psikologi hingga kehilangan pekerjaan [2] menempatkan wanita sebagai pihak yang paling rentan mengalami tekanan terutama ekonomi [3]. Peran wanita dalam keluarga terutama ibu menjadi semakin kompleks padahal tiang utama keluarga berada pada seorang wanita atau istri atau ibu [4] yang banyak dari mereka tidak dibekali cukup pengetahuan dan keterampilan untuk menghadapi dampak pandemi covid-19.…”
Section: Pendahuluanunclassified